The future dental workforce in Malaysia: Recruitment, training, retention, and team working - Che Musa, Muhd Firdaus; Gallagher, Jennifer E.; Bernabe, Eduardo (2014)
Malaysia has extended their dental workforce in order to meet the growth of population; poor oral health status; and oral health need and demand. Given this, it is vital to explore the view of students on this issue. The specific objective for this study is to explore the motivation of dental students in selection of dentistry as a professional career in relation to individual (demographic and socio-economic factors) and school characteristics.